Family Fun Night, Kansas State University Symphony Orchestra Concert - Dirks, Rachel; Cranford, Jerry Jay (Kansas State University; School of Music, Theatre, and Dance, 2019)
October 23, 2018 7:30 PM McCain Auditorium Program: Jerry Jay Cranford - An Introduction to the Orchestra Camille Saint-Saens - Carnival of the Animals Sergei Prokofiev - Peter and the Wolf Leonard Bernstein - Mambo, from West Side Story